Faktor-faktor penentu niat beli produk pakaian - Vinka Vanlia Sianata; Keni Keni (Universitas Kristen Maranatha, 2023)
Clothing business is experiencing rapid development following ongoing trends, creativity, and lifestyle, resulting in intense competition among these businesspeople. One of the things that can create high sales to outperform competitors is a high consumer purchase intention. This research investigates the effects of aesthetic, value consciousness, and store image on a brand's clothing products purchase intention which are mediated by emotional value and attitude. An online questionnaire was used to collect 252 data and the data were analyzed using PLS-SEM. The findings revealed that (1) Aesthetic influences purchase intention positively and significantly, (2) Emotional value influences purchase intention positively and significantly, (3) Attitude influences purchase intention positively and significantly, (4) Aesthetic influences emotional value positively and significantly, (5) Store image influences attitude positively and significantly, (6) Emotional value positively and significantly mediates the relationship between aesthetic and purchase intention, and (7) Attitude positively and significantly mediates the relationship between store image and purchase intention. This research shows that a high aesthetic of clothing products can affect emotional value and purchase intention. In addition, a good store image can influence attitude and purchase intentions. Therefore, clothing manufacturers and retail stores should consider these determinants in selling their clothing products to create its competitive advantages.